Ibn Abi El-Isboa El-Masseri’s Contribution to Critical and Rhetoric Terminology in his books: ‘Tahrir El-Tahbir’and ‘Badia El-Quran’. - Saioud, Fawzia (Journal of Human Sciences, 2021)
The critical and rhetorical terms constitute the primary entrance to the understanding of our ancient Arabic literature. Due to their awareness of the importance of critical and rhetoric terms, classical scholars attempted to contribute significantly in this regard. Ibn Abi El-Osboa El-Masseri’ is considered as one of the eminent figures who laid the foundations for critical and rhetorical terminology through two important books, namely: ‘Tahrir El-Tahbir’ and ‘Badia El-Quran’.